PROBLEMS OF AL-SHARF IMPLEMENTATION IN SHARIA BANKING (STUDY LITERATURE) - Simahatie, Mai; Siregar, Saparuddin; Sugianto, Sugianto (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study aims to analyze the problems that occur in the implementation of the Sharf contract in Indonesian Islamic banking, this research method is a descriptive qualitative research design with Literature Review or literature review. The results of this study are currency exchange is allowed when if it can be proven that there are no elements of gharar, maisir, usury and juhala, Al-sarf which is allowed in Islamic Sharia is only Spot Transactions while Forward Transactions and Swap Transactions are unlawful, There are problems in the implementation of Al -Sharf such as there should be no delay in payment, it is difficult to identify the customer's purpose for exchanging currency, while it is known that the Al-sarf transaction should not be carried out for the purpose of speculation (chance) or because there is a need for a transaction or as a precaution (savings). And the lack of customer literacy in knowing how to calculate or determine the exchange rate, how to calculate the currency exchange rate itself, so that in Al-Sharf transactions it can cause gharar because it is not understood by both parties to the transaction.